Angels and Heavenly Power: Maimonides' Rationalism Versus Mysticism and Duplicity of the Throne - Taub, Emmanuel (2017)
Figure of angels is present in Jewish biblical tradition and in Jewish  intertestamental literature. Even though researchers speculate on the lack of a “Jewish angelology”, the angel figure plays a leading role in the administration of Heaven and Earth. From the characterization of the figure of the angels in Maimonides, this paper seeks to understand why heattempts to rationalize the angelology and the political-theological implications of that. Specifically, we are going to analyze the role of angels in the universe administration and in the relation with men, as well as in its dispute with the heavenly power.